A Novel Toolkit to Improve Percutaneous Subxiphoid Needle Access to the Healthy Pericardial Sac. - Ludwig, Daniel R.; Menon, Prahlad G.; Fill, Brian; Gartner, Mark; Schwartzman, David (Journal of Cardiovascular Electrophysiology, 2015)
Pericardial Access Toolkit Introduction The current practice of percutaneous subxiphoid needle access to the 'healthy' pericardial sac has significant limitations. We sought to examine the feasibility of a novel toolkit designed to improve this procedure. Methods and Results The toolkit included a pericardial access needle and a virtual imaging platform. The needle had a 0.036 inch outer diameter, abbreviated 25° bevel, and was electrically insulated except for two small surfaces recessed from the tip. Radiofrequency energy was delivered via these surfaces to facilitate pericardial perforation. The virtual imaging system demonstrated the needle in real time and in its entirety within the thoracic anatomy of the individual animal, which was reconstructed from computed tomographic images obtained preoperatively and registered to the operative field. In five large (40-60 kg) healthy pigs, percutaneous subxiphoid access to the sac using both anterior and posterior approaches was performed. Spatial inaccuracy was measured as the distance between the pericardial puncture site and the anterior or posterior descending coronary artery, the pericardium contiguous to which had been targeted by the needle. In each animal, pericardial access was gained at 4 discrete sites (2 anterior, 2 posterior). Inaccuracy was 4.2 ± 2.2 millimeters (range 0-8 millimeters) and did not differ significantly between anterior and posterior approaches. No damage to the epicardium or coronary arteries was observed. Conclusions Percutaneous subxiphoid access to the pericardial sac utilizing this toolkit was feasible, including safety and reasonable accuracy.